Catalytic oxidation of nitric oxide (NO) over different catalysts: an overview. Issue 16 (5th July 2017) - Hong, Zhe; Wang, Zhong; Li, Xuebing
Abstract : Nitrogen oxides (mainly NO) are one of the major air pollutants that lead to a number of environmental problems such as photochemical smog, acid rain and haze. Abstract : Nitrogen oxides (mainly NO) are one of the major air pollutants that lead to a number of environmental problems such as photochemical smog, acid rain and haze. The catalytic oxidation of NO to NO2 is regarded as a key step in NO x elimination. In recent decades, a variety of NO oxidation catalysts have been developed for possible application, which can be divided into four categories, namely, supported (including noble metals and metal oxides), multi-metal oxide, perovskite type and carbon-based catalysts. In addition, the "fast SCR" catalysts which were effective for NO oxidation were also included. This paper reviewed the recent progress on catalysts and evaluated the catalytic performance in NO oxidation. As well, the mechanistic investigations and SO2 /H2 O tolerance were emphasized. Finally, the perspective and the future direction of NO oxidation catalysts were presented.